(الدرس النحويّ عند الجُذاميّ تناوب حروف الجرِّ وزيادتها مثالًا) - خير الله راهي مجيد; حسن رحيمة علي (Journal of College of Education, 2019)
The explanation of leprosy is one of the widest explanations of the writer’s literature. It contains several works in the field of kebab, the structure of verbs and the structure of names. The buildings of the tripartite abstract names and that a number of names come on two buildings, the reason for this difference in the Arab tribes in the use of words, and this research mentioned the other buildings of the tripartite abstract, and there are a number of buildings denied by Ibn Qutaiba, while proved by leprosy and confirmed that it A language used as the Arabic word: salt water, and presented the views of scientists and leprosy in those buildings. Then came the mention of the trio such as more Palmim or Balawo or a thousand, and stated the leprosy that the (Menten) comes from you are not stinky as mentioned by the son of Qutaiba, and that (Moses) on the scale (activated) not actual. Then he mentioned the four buildings of the four names and that they come to build (vowel), and the leprechaun in the frog mentioned three languages, and mentioned that (Ithlib) on the zina (as) do not do as he sees Ibn Qutaiba.